Effect of mating on ovary maturation in Dactylopius coccus (Hemiptera: Coccoidea: Dactylopiidae). (2019)
The cochineal Dactylopius coccus is an industrially-important insect used to extract carminic acid (a red dye). The effect of mating on the maturation of its ovaries was determined. In order to do this, three-month old mated and virgin females were used which were counted from Opuntia ficus indica cladode infestation (in Montecillo, Mexico). The morphophysiological characteristics of the degree of maturation of their ovarioles were evaluated. Mating was not needed to start the maturation of the ovarioles, because in virgin females, a low percentage of oocytes successfully complete vitellogenesis and choriogenesis; however, mating promotes both processes, since the proportion of mature oocytes produced in mated females noticeably increases. Similarly, lack of mating in D. coccus was a factor that induced degeneration of the ovarioles, and consequently, the resorption of their oocytes.